Rethinking Holocaust film reception : a British case study - Rauch, Stefanie (Lexington studies in modern Jewish history, historiography, and memory, 2021)
Though they are widely discussed by scholars, critics, and educators alike, empirically, we know little about the individual reception of Holocaust films by actual viewers. Taking Britain as a case study, this book foregrounds an analysis of audience responses to select films and explores the relationship between history, film, and memory--back cover